Evaluation by Competencies and Leadership in PALÍ Costa Rica period 2019-2022: According to the application of the motivation theory according to Stephen Robbins and Timothy Judge (National Administration Journal, 2025)
The relationship between competency evaluation and leadership in the PALÍ store chain in Costa Rica, based on Motivation Theory, addresses an approach focused on how these organizational practices influence the professional growth of employees. Through a case study, the leadership and evaluation processes applied at PALÍ are examined, highlighting the importance of competencies and experience. It also includes a review of relevant motivational theories, such as those proposed by Alderfer and Bandura, which provide a comprehensive view of how employees are motivated and develop within the organization
Keywords: Motivation theory; competency assessment; organizational psychology